Protective effect of hydrogen-rich saline against radiation-induced immune dysfunction - Zhao, Sanhu (BlackWell Publishing Ltd, 2014)
Recent studies showed that hydrogen can be used as an effective radioprotective agent through scavenging free radicals. This study was undertaken to evaluate the radioprotective effects of hydrogen on immune system in mice. H(2) was dissolved in physiological saline using an apparatus produced by our department. Spleen index and histological analysis were used to evaluate the splenic structural damage. Spleen superoxide dismutase, GSH, MDA were measured to appraise the antioxidant capacity and a DCF assay for the measurement of radical oxygen species. Cell apoptosis was evaluated by an Annexin V-FITC and propidium iodide staining method as well as the apoptotic proteins such as Bcl-2, Bax, caspase-3 and c-caspase-3. CD4+ and CD8+ T cells subtypes were detected by flow cytometry with FITC-labelled antimouse CD4 and PE antimouse CD8 staining. Real-time PCR was utilized to determine the CD4+ T cell subtypes and related cytokines. Our study demonstrated that pre-treatment with H(2) could increase the spleen index and attenuate the radiation damage on splenic structure. Radical oxygen species level was also reduced by H(2) treatment. H(2) also inhibited radiation-induced apoptosis in splenocytes and down-regulated pro-apoptotic proteins in living mice. Radiation-induced imbalance of T cells was attenuated by H(2). Finally, we found that H(2) could regulate the polarization of CD4+ T cells and the level of related cytokines. This study suggests H(2) as an effective radioprotective agent on immune system by scavenging reactive oxygen species.